The Relationship Between Single and Mixed Worm Infections and the Nutritional Status of Students at SDN 060824 Medan City - Simaremare, Edwin Sani Erico; Nasution, Sri Wahyuni; Fadillah, Qori (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2024)
Worm infections are a significant health issue among children, especially in areas with inadequate sanitation. This study aims to identify the results of fecal examinations for worm infections in children at SDN 060824, Medan City, and examine the relationship between single and mixed worm infections and their nutritional status. This research uses an observational analytic method with a cross-sectional approach. The sample consists of 50 students selected randomly, with data collected through fecal examination and nutritional status measurement. The results indicate that 4% of students tested positive for worm infections, while 96% were uninfected. Statistical analysis revealed no significant relationship between worm infections and students' nutritional status (p>0.05). This study concludes that worm infections among students in the study location do not directly impact their nutritional status. These findings provide a basis for the government and health agencies to focus on broader preventive programs for worm infections to support the overall health of children.